Fenomena Mahasiswa Kurang Mampu yang Berwirausaha Sambil Kuliah (Studi Fenomenologi) - Sopian Sopian; Ana Fitriana Poerana; Weni Adityasning Arindawati (Peneliti.net, 2022)
Students are one of the drivers of a nation's economic growth, which is expected to be able to build the Indonesian economy so that it is more advanced and developed. The purpose of the research is to reveal the motives, experiences, and meanings of underprivileged students who are entrepreneurs while studying. This study utilizes descriptive qualitative methods as well as Schutz's phenomenological framework. The research was conducted on the campus of the Faculty of Islamic Religion, As Syafi'iyah University, and the off-campus environment where underprivileged students work in the Bekasi area. This research was carried out in stages, starting from September 15, 2022, to October 25, 2022. Data collection techniques included observation, interviews, recording, note-taking, and literature studies. The research data were analyzed through three activities, including data reduction, data presentation, and conclusion. The results of the analysis show that the motives of underprivileged students who are entrepreneurs while studying include incentives, parental interaction, and identification motives. Experience gained from underprivileged students who are entrepreneurs while studying, including improving management skills; the existence of social interactions and social actions in the form of support and assistance for entrepreneurship capital from parents; and getting support and work partners. The meaning that is formed from underprivileged students who are entrepreneurs while studying, including time management abilities; considered noble because it can help ease the economic burden of parents, and entrepreneurship are activities that are considered not prestigious for some students.